Death is not enough - Rose, Karen, 1964- (Rose, Karen, 1964- Baltimore novels., 2018)
In his work as a defense attorney in Baltimore, Thorne has always been noble to a fault--specializing in helping young people in trouble just as someone did for him when he was younger. He plays the part of the bachelor well, but he secretly holds a flame for his best friend and business partner, Gwyn Weaver, a woman struggling to overcome her own demons. After four years, he thinks he might finally be ready to confess his feelings, come what may. But his plans are derailed when he wakes up in bed with a dead woman--her blood on his hands and no recollection of how he got there. Whoever is trying to frame Thorne is about to lead him down the rabbit hole of his past, something he thought he had outran long ago. Thorne must figure out who has been digging into his secrets, how much they know, and how far they will go to bring him down . . .